Optimalisasi P3DN dalam Pengadaan Barang/Jasa Pemerintah Daerah: Pendampingan dan Sosialisasi Kebijakan P3DN di Lingkungan Pemerintah Kota Bekasi - Jasan Supratman; Didin Sjarifudin; Alloysius Vendhi Prasmoro (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2026)
The Domestic Product Utilization Enhancement Program (P3DN) is a strategic government policy aimed at strengthening national industry through optimizing government spending. However, the implementation of P3DN in goods/services procurement still faces various challenges, particularly related to understanding regulations, selecting domestic products, and meeting Domestic Component Level (TKDN) requirements. This community service activity aims to improve the understanding and capacity of Bekasi City Government officials in implementing the P3DN policy in the goods/services procurement process. Implementation methods included workshops, regulatory outreach, interactive discussions, and technical assistance related to the use of domestic products. The results of the activity indicated an increase in participants' understanding of the legal basis for P3DN, the mechanism for selecting domestic products, the obligation to use products with a certain TKDN value, and the control of the use of imported products. This activity also resulted in recommendations for the development of internal regional policies to strengthen the implementation of P3DN. By increasing the capacity of regional officials, it is hoped that the use of domestic products in government goods/services procurement will increase, thus positively impacting national industrial growth and the regional economy.